2008
DOI: 10.1111/j.1651-2227.2008.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of delayed first voiding in newborn

Abstract: Delayed voiding appears to be related to a prolonged and stressful birth. Laboratory findings in the first urine suggest increased AVP and aldosterone secretion in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…AVP is a neurophyseal peptide hormone which among other functions regulates fluid balance. In our two earlier studies we showed AVP hypersecretion to induce transient fluid retention in response to prolonged or otherwise stressful birth in healthy term infants [7], [8]. This stress response appears to be purposeful and is evidently physiological, unlike the fluid retention with VLBW infants observed in our present study.…”
Section: Introductionsupporting
confidence: 53%
“…AVP is a neurophyseal peptide hormone which among other functions regulates fluid balance. In our two earlier studies we showed AVP hypersecretion to induce transient fluid retention in response to prolonged or otherwise stressful birth in healthy term infants [7], [8]. This stress response appears to be purposeful and is evidently physiological, unlike the fluid retention with VLBW infants observed in our present study.…”
Section: Introductionsupporting
confidence: 53%
“…Increased AVP levels at birth have been linked to delayed first voiding in newborns ( 93 , 115 ), and copeptin concentrations at birth are inversely related to postnatal weight loss by day 3 of life ( 86 ). Reducing urinary water loss at birth until the enteral supply picks with the establishment of lactation appears to be a prudent strategy, and cesarean section without any previous labor deprives the newborn infant of the wave of fetal AVP, which serves as a preemptive adaptation.…”
Section: Avp In Healthy Neonatesmentioning
confidence: 99%
“…The natural delay of first voiding in newborns, [22][23][24][25] especially after prolonged complicated deliveries, 26 and our desire not to cause harm and avoid too many trials of urine sampling resulted in obtaining urine cultures only in 61% of the study group, three-quarters of them in the first 24 hours and only a quarter between 24 and 72 hours. The small number of positive urine cultures further limited our ability to draw definite conclusions, especially regarding possible differences in the rate of UTI in the first 24 versus the next 24 to 72 hours of life.…”
Section: Discussionmentioning
confidence: 99%